The new encyclopedia of Southern culture. - Walker, Melissa, 1962-; Cobb, James C. (James Charles), 1947-; Wilson, Charles Reagan; Thomas, James G., Jr; Abadie, Ann J. (New encyclopedia of Southern culture., 2008)
New Encyclopedia of Southern Culture: Volume 11: Agriculture and Industry.